A Molecular Perspective on Mitochondrial Membrane Fusion: From the Key Players to Oligomerization and Tethering of Mitofusin - De Vecchis, Dario; Brandner Giménez, Astrid; Baaden, Marc; Cohen, Mickael M; Taly, Antoine (Journal of Membrane Biology, 2019)
Mitochondria are dynamic organelles characterized by an ultrastructural organization which is essential in maintaining their quality control and ensuring functional efficiency. The complex mitochondrial network is the result of the two ongoing forces of fusion and fission of inner and outer membranes. Understanding the functional details of mitochondrial dynamics is physiologically relevant as perturbations of this delicate equilibrium have critical consequences and involved in several neurological disorders. Molecular actors involved in this process are large GTPases from the dynamin-related protein family. They catalyze nucleotide-dependent membrane remodeling and are widely conserved from bacteria to higher eukaryotes. Although structural characterization of different family members has contributed in understanding molecular mechanisms of mitochondrial dynamics in more detail, the complete structure of some members as well as the precise assembly of functional oligomers remains largely unknown. As increasing structural data become available, the domain modularity across the dynamin superfamily emerged as a foundation for transfering the knowledge towards less characterized members. In this review, we will first provide an overview of the main actors involved in mitochondrial dynamics. We then discuss recent example of computational methodologies for the study of mitofusin oligomers, and present how the usage of integrative modeling in conjunction with biochemical data can be an asset in progressing the still challenging field of membrane dynamics.
Keywords: Dynamin-related proteins; Fzo1; Mitochondrial dynamics; Mitochondrial fission; Mitochondrial fusion; Mitofusin